Isolation and Screening of Proteolytic Bacteria Isolated from the Digestive Tract of Pangasius Catfish Patin (Pangasius hypophthalmus) - Zafrida, Siska; Lasmini, Titi; Hartini, Hartini; Aruan, Anggi Agustina (Jurnal Analis Medika Biosains (JAMBS), 2026)
The demand for protease enzymes in Indonesia has exhibited a significant upward trend; however, domestic large-scale production capacity remains limited. To mitigate dependency on imports, strategic efforts to develop indigenous protease production are essential. This study aims to identify and isolate protease-producing bacteria from the digestive tract of catfish (Pangasius hypophthalmus). This research employed an observational method with a cross-sectional design. Samples were obtained from the stomach of the catfish and subsequently inoculated into Brain Heart Infusion (BHI) media. Bacterial isolation was performed using Blood Agar Plate (BAP) and MacConkey Agar. The proteolytic activity of the resulting isolates was evaluated on Skim Milk Agar (SMA), followed by macroscopic and microscopic characterization. The study yielded three pure isolates; however, screening for proteolytic activity revealed that only one isolate, designated as PHS1, exhibited protease production. The proteolytic activity was characterized by the formation of a 2 mm clear zone (lysis zone) with a proteolytic index of 3. Microscopic analysis identified the isolate as a Gram-positive, spore-forming bacterium.